If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -6) + (x + 7) = 0 Reorder the terms: (-6 + 2x) + (x + 7) = 0 Remove parenthesis around (-6 + 2x) -6 + 2x + (x + 7) = 0 Reorder the terms: -6 + 2x + (7 + x) = 0 Remove parenthesis around (7 + x) -6 + 2x + 7 + x = 0 Reorder the terms: -6 + 7 + 2x + x = 0 Combine like terms: -6 + 7 = 1 1 + 2x + x = 0 Combine like terms: 2x + x = 3x 1 + 3x = 0 Solving 1 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 0 + -1 3x = 0 + -1 Combine like terms: 0 + -1 = -1 3x = -1 Divide each side by '3'. x = -0.3333333333 Simplifying x = -0.3333333333
| 25-n^2=0 | | 23x-5=0 | | 12x-4x^2-9=0 | | 12q^2-17q+5=0 | | 6(x+2)=2(x+10) | | 25b+11-6b^2=0 | | 8x/6=72/54 | | 0.1q-0.2(3q+4)=-0.3(5q+3) | | 3x^3-10x^2-23x-10=0 | | k^2-2k+1=0 | | 0.15(w+2)=0.3+0.2w | | 10-3(2b+4)=-4b-2(5-b) | | 5x^2-21x+18= | | 7-33x+20x^2=0 | | 0.2(6n+5)=0.5(2n-8)+3 | | 1.5-3y=-48.5 | | (2/7)+(1/3x)-(1/4)=(2/3x) | | 2(x+4)+8=4(x+7) | | 2n-12=0 | | y=3(-0.375)+8 | | 3w-2(0.5w+1)=-4(2+w) | | x+9x-20=90 | | 3/8+7/8 | | 5x+3x+8=5 | | 3k+5-3k=8 | | 10=5+.50d | | q=2w+2p | | 175^2-7/15m-3 | | 32+a=0 | | 2x+3(5-x)-12=4(x+2) | | 8c=-8 | | m-6=0 |